Tyrosine hydroxylase of the brain and it’s regulation by glucocorticoids - E. V. Sukhareva; T. S. Kalinina; V. V. Bulygina; N. N. Dygalo (Вавиловский журнал генетики и селекции, 2016)
Early life stress events can produce long-lasting changes in neurochemistry and behaviors related to monoamine systems, with increased risks of cardiovascular, metabolic, neuroendocrine, psychiatric disorders, generalized anxiety and depression in adulthood. Tyrosine hydroxylase (TH), the key enzyme for catecholamine synthesis, also plays an important role in the activity of the noradrenergic system and may be a target for glucocorticoids during the perinatal programming of physiological functions and behavior. Administration of hydrocortisone or dexamethasone to female rats on day 20 of pregnancy and to 3-day-old neonatal pups significantly increased TH mRNA levels (real-time PCR) and enzyme activity as well as protein levels determined by ICH in the locus coeruleus. Moreover, our treatment led to increase in TH mRNA levels in 25- and 70-day-old animals, as well as an increase in enzyme activity in the brainstem and cerebral cortex of adult rats. The long-term changes in TH expression are limited by the perinatal period of development. Administration of hormones on day 8 of life was not accompanied by changes in TH mRNA levels or enzyme activity. Glucocorticoids use several mechanisms to bring about transactivation or transrepression of genes. The main mechanism includes direct binding of the hormone-activated GRs to glucocorticoid responsive elements (GREs) in the promoter region of genes. However, despite optimistic claims made the classical GRE was not found in the TH gene promoter. Protein – protein interactions between hormone-activated GR and other transcription factors, for example, AP-1, provide an additional mechanism for the effects of glucocorticoids on gene expression. An important feature of this mechanism is its dependence on the composition of proteins formed by AP-1. Hormone-activated GRs are able to enhance gene expression when AP-1 consists of the Jun / Jun homodimer, but do not do that when AP-1 appears as the Jun / Fos heterodimer. Furthermore, as has been shown recently, the GRE / AP-1 composite site is the major site of interaction of glucocorticoids with  the TH gene in the pheochromocytoma cell line. Ontogenetic variation in the expression of Fos and Jun family proteins, which affects their ratio, can be one of the reasons for the TH gene regulation by glucocorticoids at near-term fetuses and neonates. However, to date this hypothesis has been supported only by in vitro data, and the existence of this mechanism in in vivo conditions needs to be explored in further studies.